ENDORPHIN MASSAGE EFFECT ON BACK PAIN IN THIRD TRIMESTER PREGNANT WOMEN - Miftahul Munir; Aris Puji Utami; Dwi Kurnia Purnama Sari; Ina Sholikhatin (UNIVERSITAS AIRLANGGA, 2022)
Background : Back pain during pregnancy was experienced by many women at certain times during their pregnancy, usually in the third trimester of pregnancy. Efforts to reduce pain can use pharmacological and non-pharmacological methods, by providing anti-pain drugs carried out by health workers and non-pharmacological methods can be done by health workers or families, one of which is endorphin massage therapy. The purpose of this study was to determine the effect of Endorphin Massage on back pain in third trimester pregnant women. Methods : This study used Pretest-Posttest Control Group design. Samples were taken from the population that met the inclusion criteria at PMB Faufatul Zuhriyah from June to August 2021 as many as 30 respondents with purposive sampling. The independent variable was Endorphin massage, while the dependent variable was back pain in third trimester pregnant women. Instrument using Endorphin massage technique checklist and questionnaire, visual analog scale (VAS). Results : the effect of endorphin massage on back pain in third trimester pregnant women with the Mann-Whitney test obtained a Z-count of -4.237 with a p-value of 0.000 (p-value <0.05). Conclusion : there was an effect of endorphin massage on back pain in third trimester pregnant women at PMB Faufatul Zuhriyah, Glodog Village, Palang District, Tuban Regency in 2021. It was expected that midwives can apply endorphin massage techniques to reduce back pain in third trimester pregnant women and can also be applied to pregnant women for relaxation. Keyword : Endorphin Massage, Back Pain, Third Trimester